Short‐term toxicity of 1‐methylnaphthalene to Americamysis bahia and 5 deep‐sea crustaceans. (22nd September 2017) - Knap, Anthony; Turner, Nicholas R.; Bera, Gopal; Renegar, D. Abigail; Frank, Tamara; Sericano, Jose; Riegl, Bernhard M.
Abstract: There are few studies that have evaluated hydrocarbon toxicity to vertically migrating deep‐sea micronekton. Crustaceans were collected alive using a 9‐m 2 Tucker trawl with a thermally insulated cod end and returned to the laboratory in 10 °C seawater. Toxicity of the polycyclic aromatic hydrocarbon 1‐methylnaphthalene to Americamysis bahia, Janicella spinacauda, Systellaspis debilis, Sergestes sp., Sergia sp., and a euphausiid species was assessed in a constant exposure toxicity test utilizing a novel passive dosing toxicity testing protocol. The endpoint of the median lethal concentration tests was mortality, and the results revealed high sensitivity of the deep‐sea micronekton compared with other species for which these data are available. Threshold concentrations were also used to calculate critical target lipid body burdens using the target lipid model. Environ Toxicol Chem 2017;36:3415–3423. © 2017 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC